Nikolas Dimakis and Tamara M. Dijkstra (eds) Mortuary Variability and Social Diversity in Ancient Greece: Studies on ancient Greek death and burial. - Osborne, Robin (Journal of Greek Archaeology, 2023)
pp. ii + 195. 104 figures. Oxford: Archaeopress. 2020. ISBN 978-1-78969-442-0 paperback £35.00; ISBN 978-1-78969-443-7 e-Pdf